Avaliação da Potência no Paraciclismo de Amputados - Fernandes, Karina Alves (2019)
The practice of cycling can help rehabilitate people with lower limb amputation, since it does not expose this region to high impact loads, as well as promote greater social inclusion and avoid sedentary lifestyle. However, in general, commercial prostheses are designed for walking or running activities and are costly. Thus, this study aims to evaluate the biomechanical behavior of cyclists with transtibial amputation from the development of a power evaluation equipment, through the analysis of the load applied to the pedals. This system is associated with the development of a transtibial prosthesis of varying length, low cost and that is fixed directly to the pedal through a cycling cleat. The lower articular angles were also analyzed by means of filming. To obtain a comparison parameter, a pilot test was performed with a cyclist without amputation. It was observed that the contribution of the cyclist's legs without amputation in the total power production was approximately symmetric. While for the two cyclists with transtibial amputation, using a reference prosthesis, it was smaller for the amputated leg, contributing at most 39.11%. It was found that reducing the length of the crank can promote an increase of up to 9.53% in power, using the reference prosthesis. For the prosthesis developed, the maximum power produced by the amputated leg was 55.72% of the total power, for prosthesis lengths of 143 mm and of crank of 170 mm. However, the prosthesis and crank lengths that provided greater symmetry in power generation were 143 mm and 160 mm, respectively. These values correspond to 50.08% of the total power to the amputated leg and 49.92% of the total power for the leg without disability. The pedaling technique used by the athlete changed in some tests, with a possible tendency of the non-disabled leg to pull the pedal in the recovery phase, aiding the leg amputated in the propulsion phase, for a cadence of 50 rpm.